Parenting Styles and Student’s Level of Behavioral Compliance: The Case of Jose P. Laurel Sr. High School - Suzette P. Cagurangan*; Ardrian D. Malangen,MAEd, (European Journal of Life Safety and Stability (2660-9630), 2023)
At some point in many people's lives, most adults become parents. While most of them strive to be good at becoming one, some find themselves bewildered and disappointed by the seemingly unending responsibilities of being a parent. As both parents of toddlers and teenagers can testify, such challenges can be seen from birth to teenage years. The purpose of the study is to determine the level of student's behavioral compliance that is associated with the parenting styles they experienced in their families. A sample size of 350 randomly selected respondents were involved in the study. The study utilized a descriptive correlational design to determine the level of student compliance and the parenting styles of parents. Based on the findings and results the parent-respondents in the study revealed an authoritative style as their form of parenting their children and showed a high level of compliance in terms of following school policies. This creates a positive impression among the respondents since they show a high dedication towards studies and school activities, rules and regulations. Hence, the students should continue demonstrating high dedication towards studies and activities and consistently follow school rules and regulations and parents should explore other effective aspects of each parenting style that may be used in different situations. They should learn how and when to apply the different parenting styles.